The newspaper´s destiny: the Folha de S. Paulo, O Globo and O Estado de S. Paulo in the information society - Pernisa Júnior, Carlos (Brazilian journalism research, 2009)
Where is the newspaper going? Is it doomed to disappear? Are the major Brazilian newspapers following the same course as the international press? Will the digital era put an end to journalism? Trying to answer these questions, Lourival Sant´Anna developed a research project for his master course in the Communication and Arts School of the University of São Paulo (ECA/USP), starting in 2003, having concluded his research in March 2007. The result is O destino do jornal: a Folha de S. Paulo, O Globo e O Estado de S. Paulo na sociedade da informação (The newspaper´s destiny: the Folha de S. Paulo, O Globo and O Estado de S. Paulo in the information society), published in 2008 by Editora Record in Rio de Janeiro.